ABNORMALLY INVASIVE PLACENTA: A LITERATURE REVIEW ON RISK FACTORS, DIAGNOSTIC CHALLENGES, PATHOPHYSIOLOGY, AND CLINICAL MANAGEMENT - Julia Stępień; Weronika Stachera; Maciej Sobczyk; Małgorzata Zach; Wiktoria Suchcicka; Aleksandra Borowy; Aleksandra Chajnowska; Julia Guzowska; Barbara Wołoszyn; Patrycja Rzeźnik (International Journal of Innovative Technologies in Social Science, 2025)
Placenta accreta spectrum (PAS) is a term used to describe a pathological condition characterised by abnormal placental adherence or invasion of the myometrium or extrauterine structures (1). The condition is characterised by adhesion to the myometrium in the presence of placenta accreta, invasion of the myometrium by placenta increta, and extension of the placenta through the serosa into adjacent organs, a condition known as placenta percreta(1–4) Placenta accreta spectrum disorders (PASDs) are a group of conditions characterised by the excessive adherence of the placenta, which results in the failure of the placenta to separate during birth. It is widely acknowledged that PASD represents one of the most dangerous conditions associated with pregnancy. In a considerable number of cases, the condition remains undiagnosed prior to delivery. Achieving correct prenatal diagnosis is imperative in order to reduce the burden of maternal and fetal morbidity. Despite the fact that ultrasound remains the imaging modality of choice, magnetic resonance imaging (MRI) is necessary for the evaluation of areas which are difficult to visualise using ultrasound, as well as for the assessment of the extent of placenta accreta (1,2,5,6). The implementation of effective management strategies is paramount in achieving optimal outcomes. A multidisciplinary approach is required, in addition to the establishment of adequate infrastructure (1). This article defines the characteristics, risk factors, diagnosis, management and outcomes of placenta accreta spectrum, highlighting a multidisciplinary approach.